Electricity demand and consumption in a manufacturing industry (2002)
Industrialization the world over owes its growth to the discovery of electricity. Most machines and plants are driven by electric motors; residential and industrial lighting is predominantly electrical; and the communication and entertainment industry are largely dependent 011 electricity. This paper is an analysis of the demand and consumption pattern of electricity in a manufacturing industry in Ibadan. Based on the supply pattern of the electricity to meet the needs of the organization; the paper concludes that there is a need to improve electricity supply to tile manufacturing industry to cut down its production cost which has been on the increase due to energy as one of its prime causes.